Age Moderates the Effect of Self-Paced Exercise on Exercise Adherence among Overweight Adults. (March 2020) - Lee, Harold H.; Dunsiger, Shira; Connell Bohlen, Lauren; Boyle, Holly K.; Emerson, Jessica A.; Williams, David M.
Objective: The present study tested the hypothesis that the effect of self-paced exercise on adherence to exercise programs is more pronounced with increasing age.Method: Fifty-nine low-active overweight adults (18-65 years) were encouraged to walk 30 to 60 min/day and randomized to either self-paced ( n = 30) or prescribed moderate-intensity ( n = 29) conditions.Results: The effect of study condition was moderated by age (main effect: b = 6.14, SE = 2.54, p = .02; Condition × Age: b = −11.55, SE = 3.77, p < .01), such that among participants >50 years, those in the self-paced condition exercised 6 more min/day than participants in the prescribed moderate-intensity condition ( p = .02), whereas among participants <50 years, those in the self-paced condition exercised 5.4 fewer min/day compared with those in the moderate-intensity condition ( p = .05). Affective response to physical activity did not mediate the moderating effect of age.Discussion: As age increases, adults may be more likely to adhere to self-paced versus prescribed moderate-intensity exercise.